Voltages Transient Analysis in Electric Grounding Systems. Issue 1 (February 2021) - Syafruddin, R; Fadriani, Hetty; Afiyah, Salamatul; Ramady, Givy Devira; Hidayat, Rahmad
Abstract: This paper discusses the problem of voltages transient analysis in electric grounding systems if there is a high voltage fault. With the help of the finite element theorem, the segments of the grounding systems are buried in the earth are examined, and the parameters are calculated. By using the traveling wave theory, it can be determined that the replacement circuit of the grounding rod segments, then by analyzing the electrical circuit, the voltage transient at each finite node can be calculated at the time of the fault, where the magnitude voltage transient of the fault must be known. The above method can be applied to determine the voltages transient analysis in electric grounding systems for both the rod grounding system and the grid grounding system. This voltages transient analysis in electric grounding systems is analyzed for equipment security and personal safety.